Physicochemical, tensile, and thermal characterization of new natural cellulosic fibers from the stems of Sida cordifolia. Issue 6 (2nd November 2018) - Manimaran, P.; Prithiviraj, M.; Saravanakumar, S.S.; Arthanarieswaran, V.P.; Senthamaraikannan, P.
ABSTRACT: Natural fibers are the one worthy substitute for replacing synthetic fibers and used as a polymer reinforcement due to their eco-friendly nature. This investigation deals with the newly identified Sida cordifolia fibers (SCFs) characterized by chemical analysis, single fiber tensile test, thermogravimetric analysis (TGA/DTG), Fourier transform-infrared spectroscopy (FT-IR) analysis, X-ray diffraction (XRD), and atomic force microscopy (AFM). The chemical constituents of SCFs contains cellulose (69.52%), hemicellulose (17.63%), and lignin (18.02. %). The SCFs are thermally stable up to a temperature of 338.2°C evidenced by TGA analysis. The X-ray diffraction confirmed that SCFs were rich in cellulose fraction with a crystallinity index of 56.92%.